Enhancing and Assessing Group and Team Learning in Architecture and Related Design Contexts : Final Report. - Tucker, Richard; Abbasi, Neda; Thorpe, Graham R.; Ostwald, Michael J.; Williams, Anthony P.; Wallis, Louise; Kashuk, Sam (Office for Learning and Teaching, 2014)
Architects must be able to design as part of a team, yet this essential professional competency is largely neglected by architecture schools. This project advances best-practice models of teaching and assessing teamwork within the emotive and highly subjective learning context of creating architecture. Three questions in particular need answering: how do we teach teamwork skills in the context of design?, how do we assess teamwork skills?, and how do we fairly assess individual contribution to team designs? The project proposes curriculum renewal via a structured framework for teaching teamwork with an associated suite of assessment strategies and tools. This framework will assist teachers of architecture (and other design and applied arts disciplines) to: develop innovative approaches to collaborative learning in multidisciplinary and monodisciplinary contexts, structure group work and team design within curricula, develop graduate attributes for teamwork, and assess team design in a consistent, transparent and objective manner to support team-working skills and increased learner confidence. This document is the final report from the project.